Analisis Pengaruh Kemampuan Berpikir Kritis Terhadap Pemahaman Konsep Gelombang Elektromagnetik Mahasiswa Pendidikan Fisika - Anggi Diana Pramudita; Elsa Rahmawati; Lya Himmatul Ilmi; Shofira Amatullah; Zepyra Damayanti; Sudarti .; Subiki . (Peneliti.net, 2023)
The aim of this study was to examine the influence of critical thinking abilities on the understanding of electromagnetic wave concepts among physics education students. To assess the impact of students' critical thinking abilities on their understanding of the subject matter, data was collected through the use of questionnaires. A sample of 30 physics education students participated in the study by answering questions related to their understanding of wave concept. The collected data was then analyzed using distribution tests, normal distribution tests (normalization tests), and simple linear regression. The results of the analysis indicated normality in the distribution test. X1 yielded a value of 0.404 > 0.05, indicating that the data for variable X1 followed a normal distribution. Similarly, Y1 yielded a value of 0.453 > 0.05, indicating that variable Y1 also exhibited a normal distribution. Furthermore, the results of the linearity test showed a significance value (sig.) for the linearity deviation of 0.088 > 0.05. Based on these results, it can be concluded that there is a significant linear relationship between the critical thinking skills variable (X) and the concept comprehension variable (Y). The simple linear regression test revealed a correlation (R) value of 0.723 between critical thinking abilities and the understanding of electromagnetic wave concepts. This correlation value indicates a positive relationship between the two variables. The ANOVA test demonstrated a significance level of 0.000 < 0.05, with an F value of 25.155 > F table 4.26. This implies that the regression model can be used to predict the variable of understanding wave concept material, suggesting a simultaneous influence between the critical thinking skills variable (X) and the concept comprehension variable (Y) in the wave material. In conclusion, this study sought to examine the impact of critical thinking abilities on the understanding of electromagnetic wave concepts among physics education students. The results indicate a significant and positive relationship between these variables, thereby providing insights into the importance of critical thinking in enhancing concept comprehension.